Chapter 4 The Newfoundland and Labrador Anti-Sealing Movement Experience - Burke, Danita Catherine (Taylor & Francis, 2023)
Chapter 4 explores how activism against seal hunting devolved into cultural violence against sealers, their families and communities in Newfoundland and Labrador. Drawing on archival research from the Centre for Newfoundland Studies, Memorial University of Newfoundland and Labrador, in additional to supplementary interview, this chapter illustrates how the Newfoundland and Labrador experiences with anti-sealing protesters escalated to the normalization of cultural violence in the 1970s-1980s as a means to destabilize the sealing industry and groups associated with it.